Pengaruh Penggunaan Media Pembelajaran Berbasis Game Pada Aplikasi Scratch Terhadap Minat Belajar IPA Siswa Kelas V UPT SPF SD Negeri Kompleks IKIP I Kota Makassar - Resky Aulia; Sayidiman Sayidiman; Muhammad Irfan (CV. SINAR HOWUHOWU, 2026)
This study examined the effect of game-based learning media developed with the Scratch application on fifth-grade students' interest in science learning at UPT SPF SD Negeri Kompleks IKIP I Makassar. The study employed a quantitative quasi-experimental approach with a nonequivalent control group design. A total of 64 students participated, consisting of 32 students in the experimental class and 32 students in the control class. Data were collected through a ten-item learning-interest questionnaire, an observation sheet, and documentation. Descriptive statistics, the Shapiro-Wilk normality test, Levene's homogeneity test, an independent-samples t-test, and N-Gain analysis were performed using IBM SPSS Statistics 25. The implementation of Scratch-based learning increased from 75% (effective) in the first treatment to 90% (very effective) in the second treatment. The experimental class mean increased from 41.69 at pretest to 86.63 at posttest, while the control class reached a posttest mean of 77.81. The independent-samples t-test showed a significant difference between the groups, t(62)=5.856, p<0.001, with a mean difference of 8.813. The average N-Gain was 0.7698 (high) for the experimental class and 0.6523 (moderate) for the control class. These findings indicate that game-based learning media using Scratch has a significant and practically meaningful effect on students' interest in science learning.